EOSINOPHILIC GASTRITIS- A RARE CAUSE OF GASTRIC WALL THICKNESS: A RARE CASE REPORT - Ramesh, Kundal; Navneet, Kaur; Jasmeen Kaur, Shruti; Harpal S, Seemar; Ninder, Kumar (International Journal of Clinical and Biomedical Research, 2015)
Idiopathic eosinophilic gastroenteritis is a rare inflammatory disease of unknown origin, characterized by diffuse eosinophilic infiltration of the gastrointestinal tract, accompanied by varying abdominal symptoms related to the location, severity and depth of invasion. A 63-year old male was admitted to our hospital with complaints of abdominal pain and constipation. Physical examination revealed a distended abdomen with diffuse tenderness. Ultrasound showed free fluid in peritoneal cavity. An emergency laparotomy was performed for a diagnosis of peritonitis due to intestinal obstruction. Pylorus of stomach showed thickening of wall. A Gastric perforation with indurated and rolled margins was identified, gastrojejunostomy was performed and provisional diagnosis of malignant growth with complication of perforation was made but histologically, thickened wall of the stomach revealed dense infiltration of eosinophils and eosiniphilic gastroenteritis was diagnosed. KEYWORDS: Eosinophils, Gastroenteritis; Eosinophilic gastroenteritis; Coticosteroid.